Determination of Airport Area Accessibility, Accuracy of Flight Times, and Check-In Process Time on Airplane Passenger Satisfaction (Study at Soekarno Hatta Airport) - Farchan Hudayah; Hery Mustika; Juliater Simarmata (Dinasti International Journal of Digital Business Management, 2024)
Article on determining airport area accessibility, flight timeliness and check-in process time on airplane passenger satisfaction (Study at Soekarno Hatta Airport) within the scope of marketing management science. This article aims to create hypotheses regarding the relationship between factors, which can then be used for further research in the field of marketing management. The research method used in this research is descriptive qualitative. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The results of this literature research include: 1) Accessibility influences aircraft passenger satisfaction at Soekarno Hatta Airport; 2) Punctuality of flight times influences aircraft passenger satisfaction at Soekarno Hatta Airport; and 3) The speed of the check-in process influences the satisfaction of airplane passengers at Soekarno Hatta Airport.